Progressividade tributária: A agenda negligenciada - Sérgio Wulff Gobetti; Rodrigo Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper presents a critical assessment of income and profit taxation in Brazil. It discuss how tax cuts for capital income during the eighties and nineties, following mainstream policy recommendations, have constrained the redistributive role of the income tax. The analysis is based on administrative tax data ant its main findings points out for a very high top incomes concentration, low degree of income tax progressivity and violation of the principles of horizontal and vertical equity at the very top of the distribution. These distortions are caused mainly by the complete relief from taxes of the dividends in Brazil. A very unusual tax benefit among developed and developing countries. Policy recommendations prescribe to recuperate a tax reform focused on progressivity, a theme that has gained great attention in recent years since Piketty (2014).
Keywords: H24; N46; E62; 330; income tax; progressivity; tax reform